Frase Nomina Bahasa Buol - Ali Karim (Multilingual, 2016)
The main focus of the research is noun phrase in Buol language. This research aims todescribe the noun phrase in Buol language and its patterns. The research’s objectivesis to describe the noun phrases and its patterns in Buol language. Steps to be taken inthis study begins with data collection. In obtaining data, researchers usedquestionnaire related to the noun phrase. Recording technique and notes-taking areused in this method. The data were analyzed by using read-marker method anddistributional method in expand technique. The result shows that the noun phrase inBuol language includes attributive noun phrase and coordinative noun phrase. TheAttributive noun phrase has some patterns: (1)stem-modifier, (2)modifier-stem, (3)modifier-stem-modifier. While the coordinative noun phrase has a single pattern, thatis multistem pattern.